Rock mass response to mining activities : inferring large-scale rock mass failure - Szwedzicki, Tadeusz; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Mining activities may result in rock mass deterioration and instability that may lead to failure both in underground and open pit mines. Such deterioration represents a safety risk and may result in substantial financial losses. Rock mass response may lead to ground subsidence, fall of ground/caving, inundation, pillar collapse, seismic activities and slope and tailings dam instability. Each response is preceded by warning signs and precursors, which are identified in this book, with a view to providing guidelines for prediction and amelioration of damage to mining structures. Furthermore, case studies of both large scale ground deterioration leading to collapse and geotechnical mine disasters are presented. Identifying risks and monitoring geotechnical precursors and warning signs allows for safe and productive mining.
chapter 1 Introduction / Tadeusz Szwedzicki -- chapter 2 Factors affecting rock mass response to mining / Tadeusz Szwedzicki -- chapter 3 Case studies of rock mass response to underground mining / Tadeusz Szwedzicki -- chapter 4 Case studies of rock mass response to surface mining / Tadeusz Szwedzicki -- chapter 5 Case studies of inundations / Tadeusz Szwedzicki -- chapter 6 Effect of discontinuities on the initiation of failure process / Tadeusz Szwedzicki -- chapter 7 Behaviour of rock mass prior to failure / Tadeusz Szwedzicki -- chapter 8 Rock mass behaviour during failure / Tadeusz Szwedzicki -- chapter 9 Post-failure rock mass behaviour / Tadeusz Szwedzicki -- chapter 10 Modes of failure of rock and rock mass / Tadeusz Szwedzicki -- chapter 11 Behaviour of fragmented ore / Tadeusz Szwedzicki -- chapter 12 Mitigation of rock mass response through geotechnical quality assurance / Tadeusz Szwedzicki.
Keywords: Ground control (Mining); TECHNOLOGY & ENGINEERING / Mining; TECHNOLOGY & ENGINEERING / Civil / Soil & Rock; Geotechnical Failures; Hazard Assessment; Hazard Management; Mining Hazards; Quality Assurance; Rockbursting Mines; Rock Mass Damage; Ground control (Mining); Mine accidents -- Risk assessment; Rock bursts; Rock mechanics